Adjunctive techniques to dacryocystorhinostomy: an evidence‐based review with recommendations. Issue 5 (27th September 2020) - Yim, Michael; Wormald, Peter‐John; Doucet, Manon; Gill, Amarbir; Kingdom, Todd; Orlandi, Richard; Crum, Alison; Marx, Douglas; Alt, Jeremiah
Abstract : Background: Many adjunctive techniques exist for dacryocystorhinostomy (DCR), with varying levels of supportive evidence. Methods: Literature from PubMed, EMBASE, and Cochrane Databases was reviewed between January 1990 and January 2020 to examine evidence regarding the utility of adjunctive techniques to DCR, including mucosal flap preservation, concurrent septoplasty, stenting, topical mitomycin C (MMC), and 5‐fluorouracil (5‐FU), as well as perioperative antibiotics and steroids. Recommendations were made based on the evidence found. Results: Seven adjunctive techniques used in DCR were examined. The literature supported concurrent septoplasty when septal deviation is present. Silicone stents are recommended for external DCR approaches. MMC use is optional in external DCR and revision cases. The literature does not support the routine use of silicone stents or MMC in primary endoscopic DCR. Mucosal flap preservation is optional, with evidence showing comparable results with or without utilization. The level of evidence is limited for topical 5‐FU, as well as perioperative antibiotic and steroid use. Conclusion: Recommendations for adjunctive techniques to external and endoscopic DCR surgeries can be made based on the current literature. Higher‐level studies are needed to better optimize perioperative approaches to DCR.